Lithium manganate material as well as preparation method and application thereof

By using a multi-doped material with spinel structure and a cladding layer of perovskite or spinel structure in lithium manganate, the capacity attenuation problem caused by structural changes in lithium manganate in high temperature environment is solved, and the high temperature performance and high capacity of the material are achieved.

CN119786558APending Publication Date: 2025-04-08NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411959353.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Lithium manganate is prone to structural changes in high-temperature environments, resulting in rapid attenuation of capacity, limiting its application in high-performance batteries.

Method used

The multi-doped lithium manganate material with spinel structure is used to improve the structural stability and acid-base stability of the material through the coordinated doping of high-priced doping element A and low-priced doping element B, combined with the cladding of perovskite or spinel structure.

Benefits of technology

While improving the high-temperature performance of lithium manganate, it maintains its high capacity, extends the circulation life of the material and improves the high-temperature circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786558A_ABST
    Figure CN119786558A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and provides a lithium manganate material and a preparation method and application thereof.The lithium manganate material comprises multi-element doped lithium manganate of a spinel structure, the multi-element doped lithium manganate contains a high-valence doping element A and a low-valence doping element B, and co-doping is conducted according to the average valence state E which is larger than or equal to 3.4 and smaller than or equal to 3.6; and the outer surface of the multi-element doped lithium manganate is also provided with a coating layer with a perovskite structure and / or a spinel structure. According to the method, the synergistic effect of mixed doping is fully utilized, the structural stability of lithium manganate is improved through low-valence cations, the problem of capacity reduction caused by increase of the average valence state of manganese can be solved through high-valence cations, and therefore high-capacity exertion of the material is guaranteed while the structural stability is improved and oxygen defects are reduced. Meanwhile, the coating layer with a perovskite or spinel structure is adopted, so that the coating layer has higher structural stability and acid-base stability, and the high-temperature cycle improvement effect superior to that of a conventional metal oxide coating material such as aluminum oxide can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a lithium manganate material and a preparation method and application thereof. Background Art

[0002] With the global emphasis on environmental protection and sustainable development, the electric vehicle market has ushered in a golden period of rapid development. As one of the core components of electric vehicles, the demand for power lithium-ion batteries has also surged. In lithium-ion batteries, the selection of positive electrode materials is crucial to the overall performance of the battery. The main positive electrode materials currently used in the market include lithium iron phosphate and ternary nickel cobalt manganese oxide, which dominate due to their excellent electrochemical properties.

[0003] However, lithium manganese oxide (LiMn2O4, LMO), as a potential positive electrode material, has gradually attracted attention in recent years. Compared with other positive electrode materials, the raw material cost of lithium manganese oxide is lower, which is conducive to reducing the cost of battery manufacturing. The working voltage of lithium manganese oxide is higher, usually around 4.0V, which helps to improve the energy density of the battery. In addition, the theoretical specific capacity of lithium manganese oxide is about 148mAh / g, which is close to lithium iron phosphate and can provide similar energy output. However, under high temperature conditions, lithium manganese oxide is prone to structural changes, resulting in rapid capacity decay. This is due to the increase in lattice distortion and oxygen defects caused by the Jahn-Teller effect, which in turn aggravates the dissolution of manganese ions and reduces the stability of the material, resulting in lithium manganese oxide showing a shorter cycle life during high-temperature cycling, limiting its application in high-performance batteries, so that it can only be used as a cost reduction solution for blending.

[0004] In order to overcome the performance degradation problem of lithium manganese oxide in high temperature environments, researchers have proposed a series of modification schemes, among which bulk element doping is considered to be an effective technical means. By doping with other elements, the structure of lithium manganese oxide can be stabilized, oxygen defects can be reduced, and the high temperature performance of the material can be improved. However, the existing doping process often leads to a decrease in the capacity of the material. This is because the doping element replaces a part of the manganese ions, resulting in an increase in the average valence state of manganese, thereby reducing the reversible capacity of the material. This capacity reduction weakens the market competitiveness of modified lithium manganese oxide materials.

[0005] Therefore, how to improve the high-temperature performance of lithium manganese oxide while maintaining its high capacity is the main problem facing current technology. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a lithium manganate material and its preparation method and use, wherein the lithium manganate material includes a multi-doped lithium manganate with a spinel structure, which includes a high-valent doping element A and a low-valent doping element B, which are co-doped according to an average valence of 3.4≤E≤3.6; and the outer surface of the multi-doped lithium manganate also has a coating layer with a perovskite structure and / or a spinel structure. The present invention makes full use of the synergistic effect of mixed doping, so that low-valent cations can improve the structural stability of lithium manganate, and high-valent cations can solve the capacity reduction problem caused by the increase in the average valence of manganese, thereby improving the structural stability and reducing oxygen defects while ensuring the high capacity of the material; at the same time, a coating layer with a perovskite or spinel structure is used, which has higher structural stability and acid-base stability, and can achieve a high-temperature cycle improvement effect that exceeds conventional metal oxide coating materials such as alumina.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a lithium manganate material, comprising a multi-doped lithium manganate with a spinel structure, wherein the chemical formula of the multi-doped lithium manganate is Li 1+x Mn 2-y-z A y B z O4, 0.04≤x≤0.15, y≤0.02, y+z≤0.10; A and B are doping elements, and A is a high-valent transition metal, and B is a low-valent transition metal; E A is the oxidation state of A, E B is the oxidation state of B, E is the average valence state of the doping element, and E=(E A *y+E B *z) / (y+z), 3.4≤E≤3.6; the outer surface of the multi-doped lithium manganate also has a coating layer, the coating layer includes divalent and / or trivalent transition metal elements, and the coating layer is a perovskite structure and / or a spinel structure.

[0009] The present invention achieves the effect of improving the high temperature performance of lithium manganese oxide while maintaining its high capacity. Although the traditional bulk element doping can stabilize the structure of lithium manganese oxide, reduce oxygen defects, and improve the high temperature performance of the material, it often leads to a decrease in the material capacity. This is because the doping element replaces a part of the manganese ions, resulting in an increase in the average valence state of manganese, thereby reducing the reversible capacity of the material. This capacity reduction weakens the market competitiveness of the modified lithium manganese oxide material.

[0010] To this end, first, the present invention adopts a multi-element mixed doping method of high-valent doping element A and low-valent doping element B, wherein the doping ratio of A and B is within a certain range to give full play to the synergistic effect of two transition metal elements (cations) with different valence states. By precisely controlling the doping ratio of high-valent transition metal cations and low-valent transition metal cations, that is, 3.4≤E≤3.6, the low-valent cations improve the structural stability of lithium manganese oxide, and the high-valent cations improve the average content of trivalent manganese ions to neutralize the capacity reduction problem caused by the increase in the average valence state of manganese caused by the doping of low-valent cations. Specifically, the invention proposes the concept of the average valence state E of the doping element, and limits the average valence state of high and low-valent doping elements, 3.4≤E≤3.6 to ensure that the average valence state of the high and low-valent elements incorporated is close to the average valence state of 3.5 in the initial structure of LMO, avoiding the problem of Mn 3+ and Mn 4+ The number of doping elements can be greatly increased or decreased, thereby achieving a significant improvement in the stability of the material structure while ensuring that the capacity does not decrease significantly. The definition of the average valence state E of the doping element clarifies the ratio of high-valent elements and low-valent elements doped into the LMO structure. This innovative doping method can not only improve the structural stability and reduce oxygen defects, but also ensure the high capacity of the obtained multi-doped lithium manganese oxide material (hereinafter referred to as LMO), effectively solving the problem of reduced material capacity caused by the doping process in the prior art.

[0011] Second, considering that the molecular weight of high-valent transition metal elements is heavier, the ionic radius is larger, and the difference from the ionic radius of manganese is large, it is more difficult to diffuse inside the LMO material, so high-valent transition metal elements are easily distributed near the surface and the outer surface, resulting in a lower average valence state of manganese in the near-surface and outer-surface areas, which leads to more serious dissolution of manganese and worsening of the cycle. The present invention can achieve a small amount of doping and penetration of low-valent elements in the coating agent on the outer surface of LMO particles by epitaxial coating of low-valent transition metal elements on the surface of LMO particles, neutralize the reduction in the average valence state of manganese caused by the aggregation of high-valent elements, and reduce manganese dissolution. Secondly, the outer-coated oxide can reduce the direct contact between LMO and the electrolyte, reduce the corrosion of HF, etc., further reduce manganese dissolution, and improve the cycle. The present invention is different from conventional oxide coatings such as Al2O3 and MgO. It uses a coating layer with a higher structure, acid-base stability, and a structure such as perovskite or spinel, which can achieve a high-temperature cycle improvement effect beyond conventional metal oxide coating materials. That is, the present invention forms a spinel and / or perovskite structure coating through epitaxial coating of low-valent transition metals, effectively solving the manganese dissolution problem caused by "enrichment" in the near-surface caused by the high-valent metal element doping process, and further achieving improvement and enhancement of high-temperature cycle performance.

[0012] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] In the present invention, 3.4≤E≤3.6, for example, E can be 3.4, 3.42, 3.44, 3.46, 3.48, 3.50, 3.52, 3.54, 3.56, 3.58 or 3.6, etc., preferably 3.48≤E≤3.52, that is, E is around 3.5 (E≈3.5), but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0014] In the present invention, when E < 3.4, the proportion of low-valent elements added is too high. Although the material cycle retention rate will be further improved, the charge and discharge capacity of the material will be significantly reduced. When E > 3.6, too much high-valent elements are added, and the synergistic effect of low-valent doping elements on improving structural stability is not enough to balance the negative impact of high-valent elements. 3+ As the temperature increases, the Jiang-Taylor effect intensifies and the cycle performance deteriorates to a certain extent.

[0015] As a preferred technical solution of the present invention, the A includes a transition metal element with a pentavalent or hexavalent oxidation state, and A includes at least one of Nb, Mo or W.

[0016] Preferably, the B includes a transition metal element having a divalent or trivalent oxidation state, and B includes at least one of Mg, Zn, Sr, Al, Cr, Co or Ni.

[0017] Preferably, A is further preferably Nb and / or W, and B is further preferably at least one of Mg, Sr, Al, Cr, Co, and Ni; in the chemical formula of multi-doped lithium manganate, a typical but non-limiting combination of A and B includes Nb 0.01 Cr 0.015 Sr 0.005 , Nb 0.006 W 0.004 Cr 0.018 Al 0.02 , Nb 0.006 W 0.004 Cr 0.013 Al 0.01 Mg 0.005 wait.

[0018] As a preferred technical solution of the present invention, the coating layer includes a composite oxide of a divalent and / or trivalent transition metal element; the composite oxide includes at least one of LaAlO3, LaNiO3, SrAl2O4 or ZnAl2O4, for example, typical but non-limiting examples include a combination of LaAlO3 and LaNiO3, a combination of LaAlO3 and SrAl2O4, a combination of LaAlO3 and ZnAl2O4, or a combination of SrAl2O4 and ZnAl2O4, etc.

[0019] Preferably, based on the mass of the multi-doped lithium manganese oxide as 100%, the mass of the coating layer accounts for 0.5% to 2%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., preferably 1.0% to 1.5%, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0020] In a second aspect, the present invention provides a method for preparing the lithium manganese oxide material, the preparation method comprising:

[0021] Mixing a lithium source, a manganese source, and additives containing A and B separately or simultaneously, and performing a first sintering to obtain multi-element doped lithium manganate;

[0022] The obtained multinary doped lithium manganate is mixed with a coating agent, and a second sintering is performed to form a coating layer to obtain a multinary doped lithium manganate material.

[0023] As a preferred technical solution of the present invention, the lithium source includes at least one of Li2CO3, LiOH·H2O or LiNO3. For example, typical but non-limiting combination examples include a combination of Li2CO3 and LiOH·H2O, a combination of Li2CO3 and LiNO3, or a combination of LiOH·H2O and LiNO3.

[0024] Preferably, the manganese source includes at least one of Mn3O4, MnO2, Mn2O3 or MnCO3. For example, typical but non-limiting examples of combinations include a combination of Mn3O4 and MnO2, Mn3O4 and Mn2O3, Mn3O4 and MnCO3, a combination of MnO2 and Mn2O3, a combination of MnO2 and MnCO3, or a combination of Mn2O3 and MnCO3, etc.

[0025] Preferably, the additives containing A and B separately or simultaneously include at least one of oxides, hydroxides, carbonates, oxalates or nitrates. Typical but non-limiting examples of combinations include oxides, combinations with hydroxides, combinations of oxides and carbonates, combinations of oxides and oxalates, combinations of oxides and nitrates, combinations of carbonates and nitrates, combinations of carbonates and oxalates, combinations of hydroxides and nitrates, or combinations of hydroxides and carbonates, etc., preferably oxides and / or hydroxides.

[0026] Preferably, the particle size of the additives containing A and B separately or simultaneously is ≤1 μm, for example, 1 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm, 0.5 μm, 0.4 μm, 0.3 μm, 0.2 μm, 0.1 μm or 0.05 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0027] Preferably, the amounts of the lithium source, the manganese source, and the additives containing A and B separately or simultaneously are controlled according to the stoichiometric ratio in the chemical formula of the multi-doped lithium manganate.

[0028] Preferably, the coating agent comprises a composite oxide of a divalent and / or trivalent transition metal element; the composite oxide comprises at least one of LaAlO3, LaNiO3, SrAl2O4 or ZnAl2O4.

[0029] Preferably, the particle size D of the coating agent is 50 100 nm to 5 μm, for example, 100 nm, 200 nm, 300 nm, 500 nm, 700 nm, 900 nm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.2 μm, 4.5 μm, 4.8 μm or 5 μm.

[0030] As a preferred technical solution of the present invention, the first sintering process includes firstly heating the temperature to 450-650°C, such as 450°C, 480°C, 500°C, 530°C, 550°C, 580°C, 600°C, 620°C or 650°C, at a heating rate of 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min, and pre-sintering for 4-8h, such as 4h, 5h, 6h, 7h or 8h, etc.; then continue to raise the temperature to 700-850°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C or 850°C, etc., and keep it warm for 9-11h for two-stage sintering, for example, 9h, 9.3h, 9.5h, 9.8h, 10h, 10.2h, 10.5h, 10.8h or 11h, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0031] Preferably, the first sintering is performed in an oxidizing atmosphere, which includes air and may also be oxygen-enriched air.

[0032] Preferably, after the first sintering, the sintered sample is sequentially crushed, sieved and iron-removed.

[0033] As a preferred technical solution of the present invention, the second sintering process includes first heating the temperature to 700-800°C, such as 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, at a heating rate of 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min, and then sintering for 1-3h, such as 1h, 1.3h, 1.5h, 1.8h, 2h, 2.2h , 2.5h, 2.8h or 3h, etc.; then cool to 500-650℃, for example, 500℃, 520℃, 550℃, 580℃, 600℃, 650℃ or 650℃, etc., and keep warm for 7-9h for secondary sintering, for example, 7h, 7.2h, 7.5h, 7.8h, 8h, 8.2h, 8.5h, 8.8h or 9h, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0034] Preferably, after the second sintering, the sintered sample is sequentially crushed, sieved and iron-removed.

[0035] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate contains the lithium manganese oxide material described in the first aspect.

[0036] In a fourth aspect, the present invention provides a battery, wherein the battery contains the positive electrode sheet described in the third aspect or contains the lithium manganese oxide material described in the first aspect.

[0037] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0038] Therefore, the technical solution proposes a solution of multi-mixed doping of high-valent transition metal cations and low-valent transition metal cations, making full use of the synergistic effect of mixed doping of multiple transition metal cations, low-valent cations improve the structural stability of lithium manganate, and high-valent cations improve the average content of trivalent manganese ions to neutralize the capacity reduction problem caused by the increase in the average valence state of manganese due to low-valent cation doping, thereby improving structural stability and reducing oxygen defects while ensuring the high capacity of the material. At the same time, the present invention uses low-valent transition metal elements to form a coating layer with a structure such as perovskite or spinel, which can neutralize the reduction in the average valence state of manganese caused by near-surface aggregation in high-valent elements, and is also conducive to reducing the direct contact between the internal multi-doped lithium manganate and the electrolyte, reducing the corrosion of HF, etc., further ensuring that manganese dissolution is reduced and the cycle performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a charge and discharge curve diagram of the button cell containing the lithium manganese oxide material obtained in Example 1 at the first cycle of 0.1C.

[0040] Figure 2 It is a cycle curve diagram of a button cell containing the lithium manganese oxide material obtained in Example 1.

[0041] Figure 3 It is a normal temperature / high temperature cycle curve diagram of a soft-pack full battery containing the lithium manganese oxide material obtained in Example 1.

[0042] Figure 4 This is the XPS test chart of the manganese element in the lithium manganate material obtained in Example 1.

[0043] FIG5( a ) is a SEM test image of the multi-element doped lithium manganese oxide obtained in Example 1.

[0044] FIG5( b ) is a SEM test image of the lithium manganate material obtained in Example 1.

[0045] FIG5(c) is a near-surface TEM test image of the multi-doped lithium manganese oxide obtained in Example 1.

[0046] FIG5( d ) is a near-surface TEM test image of the lithium manganate material obtained in Example 1.

[0047] FIG5(e) is an electron diffraction pattern of the surface coating layer of the lithium manganate material obtained in Example 1.

[0048] FIG6( a ) is a cross-sectional EPMA test diagram of the lithium manganate material obtained in Example 1.

[0049] FIG6(b) is a distribution diagram of the manganese element in FIG6(a).

[0050] FIG6(c) is a distribution diagram of the aluminum element in FIG6(a).

[0051] FIG6(d) is a distribution diagram of the lanthanum element in FIG6(a). DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0053] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0054] Example 1

[0055] This embodiment provides a lithium manganate material, wherein the lithium manganate material includes a multi-doped lithium manganate with a spinel structure, and the chemical formula of the multi-doped lithium manganate is Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4, the outer surface of the multi-doped lithium manganate also has a coating layer, and the coating layer includes LaAlO3.

[0056] The preparation method of the lithium manganate material comprises:

[0057] (1) First mixing: according to the chemical formula Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 The stoichiometric ratio in O4 is as follows: the corresponding masses of lithium source Li2CO3 and manganese source spherical manganese tetraoxide (D50≈6μm) are weighed respectively, and the additives niobium pentoxide, chromium trioxide and strontium oxide are simply mixed and added into a high-speed mixer for mixing at a mixing speed of 800rpm for 30min.

[0058] First sintering: After mixing, the materials are divided into saggers according to the appropriate filling amount. In an atmosphere furnace, the temperature is increased to 600°C at a heating rate of 2°C / min and maintained for 8 hours, and then continued to be heated to 750°C and maintained for 10 hours. The air atmosphere is maintained during the sintering process. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain multi-doped lithium manganate.

[0059] (2) Second Mixture: LaAlO3 (particle size D 50 =300nm), and after simple mixing with multi-doped lithium manganate, a high-speed mixer is used for mixing at a mixing speed of 800rpm for 30min.

[0060] Second sintering: the mixture is divided into saggers according to the appropriate filling amount, and the temperature is increased to 750°C at a heating rate of 2°C / min in an atmosphere furnace and maintained for 2 hours, and then cooled to 650°C and kept warm for 8 hours. The air atmosphere is maintained during the sintering process. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain lithium manganate material.

[0061] Example 2

[0062] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.925 Nb 0.006 W 0.004 Cr 0.018 Al 0.02 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is adjusted from LaAlO3 accounting for 1.5% by mass to LaNiO3 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0063] Example 3

[0064] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.965 Nb 0.006 W 0.004 Cr 0.018 Mg 0.007 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is adjusted from LaAlO3 accounting for 1.5% by mass to SrAl2O4 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0065] Example 4

[0066] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.965 Nb0.006 W 0.004 Cr 0.018 Sr 0.007 O4, the coating layer on the outer surface of the multi-doped lithium manganate is adjusted from LaAlO3 accounting for 1.5% by weight to ZnAl2O4 accounting for 1.5% by weight. Except for the above, other conditions are exactly the same as those in Example 1.

[0067] Example 5

[0068] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.964 Nb 0.006 W 0.004 Cr 0.013 Al 0.01 Mg 0.005 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is kept at 1.5% by mass of LaAlO3. Except for the above, other conditions are exactly the same as those in Example 1.

[0069] Example 6

[0070] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.965 Nb 0.01 Cr 0.019 Sr 0.006 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is kept at 1.5% by mass of LaAlO3. Except for the above, other conditions are exactly the same as those in Example 1.

[0071] Example 7

[0072] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.975 Nb 0.01 Cr0.01 Sr 0.005 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is kept at 1.5% by mass of LaAlO3. Except for the above, other conditions are exactly the same as those in Example 1.

[0073] Example 8

[0074] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate maintaining the spinel structure is Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 remains unchanged, and the mass proportion of LaAlO3 on the outer surface of the multi-doped lithium manganese oxide is adjusted from 1.5% to 1.0%. Except for the above, other conditions are exactly the same as those in Example 1.

[0075] Example 9

[0076] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate maintaining the spinel structure is Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 remains unchanged, and the mass proportion of LaAlO3 on the outer surface of the multi-doped lithium manganese oxide is adjusted from 1.5% to 2.0%. Except for the above, other conditions are exactly the same as those in Example 1.

[0077] Example 10

[0078] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate maintaining the spinel structure is Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 remains unchanged, and the mass proportion of LaAlO3 on the outer surface of the multi-doped lithium manganese oxide is adjusted from 1.5% to 0.3%. Except for the above, other conditions are exactly the same as those in Example 1.

[0079] Embodiment 11

[0080] This embodiment provides a lithium manganate material, in which the multi-doped lithium manganate maintaining the spinel structure is Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005O4 remains unchanged, and the mass proportion of LaAlO3 on the outer surface of the multi-doped lithium manganese oxide is adjusted from 1.5% to 2.5%. Except for the above, other conditions are exactly the same as those in Example 1.

[0081] Example 12

[0082] The present embodiment provides a lithium manganate material. In the preparation method of the lithium manganate material, the second sintering process is adjusted in step (2), that is, the mixture is divided into saggers according to appropriate filling amounts, and the temperature is increased to 670°C at a heating rate of 2°C / min in an atmosphere furnace and maintained for 2 hours, and then the temperature is reduced to 470°C and maintained for 8 hours. The air atmosphere is maintained during the sintering process. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain the lithium manganate material. Except for the above, the other conditions are exactly the same as those in Example 1.

[0083] Example 13

[0084] The present embodiment provides a lithium manganate material. In the preparation method of the lithium manganate material, the second sintering process is adjusted in step (2), that is, the mixture is divided into saggers according to appropriate filling amounts, and the mixture is heated to 700°C at a heating rate of 3°C / min in an atmosphere furnace and maintained for 2 hours, and then cooled to 500°C and maintained for 8 hours. The air atmosphere is maintained during the sintering process. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain the lithium manganate material. Except for the above, the other conditions are exactly the same as those in Example 1.

[0085] Embodiment 14

[0086] The present embodiment provides a lithium manganate material. In the preparation method of the lithium manganate material, the second sintering process is adjusted in step (2), that is, the mixture is divided into a sagger according to a suitable filling amount, and the mixture is heated to 800°C at a heating rate of 5°C / min in an atmosphere furnace and maintained for 2 hours, and then cooled to 650°C and maintained for 8 hours. The air atmosphere is maintained during the sintering process. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain the lithium manganate material. Except for the above, the other conditions are exactly the same as those in Example 1.

[0087] Embodiment 15

[0088] The present embodiment provides a lithium manganate material. In the preparation method of the lithium manganate material, the second sintering process is adjusted in step (2), that is, the mixture is divided into saggers according to appropriate filling amounts, and the temperature is increased to 830° C. at a heating rate of 5° C. / min in an atmosphere furnace and maintained for 2 h, and then the temperature is reduced to 680° C. and maintained for 8 h. During the sintering process, an air atmosphere is maintained. After the reaction is completed, the product is crushed, sieved (325 mesh) to remove iron and packaged to obtain the lithium manganate material. Except for the above, other conditions are exactly the same as those in Example 1.

[0089] Comparative Example 1

[0090] This comparative example provides a lithium manganate material, in which the lithium manganate material is not doped, that is, Li 1.05 Mn2O4, and its outer surface coating layer is still LaAlO3 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0091] Comparative Example 2

[0092] This comparative example provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.98 Mg 0.02 O4, that is, no high-valent transition metal doping elements are used for cooperative doping, and the outer surface coating layer is still LaAlO3 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0093] Comparative Example 3

[0094] This comparative example provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.98 Nb 0.02 O4, that is, no low-valent transition metal doping elements are used for cooperative doping, and the outer surface coating layer is still LaAlO3 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0095] Comparative Example 4

[0096] This comparative example provides a lithium manganese oxide material, in which the outer surface coating layer of the spinel structured multi-doped lithium manganese oxide is adjusted from LaAlO3 accounting for 1.5% by mass to Al2O3 accounting for 1.5% by mass. Except for the above, other conditions are exactly the same as those in Example 1.

[0097] Comparative Example 5

[0098] This comparative example provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.96 Nb 0.01 Cr 0.022 Sr 0.008 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is kept at 1.5% by mass of LaAlO3. Except for the above, other conditions are exactly the same as those in Example 1.

[0099] Comparative Example 6

[0100] This comparative example provides a lithium manganate material, in which the multi-doped lithium manganate of spinel structure is composed of Li 1.05 Mn 1.97 Nb 0.01 Cr 0.015 Sr 0.005 O4 adjusted to Li 1.05 Mn 1.977 Nb 0.01 Cr 0.009 Sr 0.004 O4, the coating layer on the outer surface of the multi-doped lithium manganese oxide is kept at 1.5% by mass of LaAlO3. Except for the above, other conditions are exactly the same as those in Example 1.

[0101] The lithium manganate materials obtained in the examples and comparative examples were characterized and tested as follows.

[0102] Ⅰ. Morphology and composition characterization:

[0103] (1) Perform SEM morphology test using Hitachi Regulus 8100 / SU 8010. A small amount of sample powder is bonded to the surface of the conductive adhesive and then tested according to the standard JY / T010-1996 to obtain the morphology information of the sample and the surface coating layer.

[0104] Figure 5(a) is an SEM image of the multinary doped lithium manganese oxide material obtained before coating in Example 1, i.e., after the first sintering, and the figure shows the outer surface morphology of the lithium manganese oxide without a coating layer; Figure 5(b) is an SEM morphology image of the lithium manganese oxide material with a coating layer after coating in Example 1, i.e., after the second sintering, and the figure shows the change in the outer surface morphology of the lithium manganese oxide after coating. The presence of an obvious coating layer can be observed, and the gaps between the primary small particles on the surface of the polycrystalline large particles are filled / covered by the coating material. Some materials are not completely melted and exist as point-like particles. The coating layer forms a relatively uniform coverage on the surface of the particles.

[0105] (2) TEM morphology test was carried out using JEM-2100F, EM-20145 produced by JEOL Ltd. A small amount of sample was ultrasonically dispersed in an ethanol solution, then dropped onto a copper mesh for testing and naturally dried before testing. The average thickness of the coating layer near the surface of the sample can be obtained. In addition, at ultra-high magnification, the coating layer area on the surface of the lithium manganese oxide material was selected for electron diffraction testing. Based on the test results, the phase structure of the coating material can be analyzed and determined. Figure 5(e) is the electron diffraction corresponding to the coating layer structure. The phase structure analysis determined that it is a perovskite structure, and it is consistent with the unit cell parameters of the LaAlO3(111) crystal plane, confirming that the coating layer is LaAlO3 with a perovskite structure, rather than a conventional mixture of aluminum, lanthanum and oxygen.

[0106] Figure 5(c) is a TEM image corresponding to the multi-doped lithium manganese oxide of Figure 5(a), which shows that there is no coating layer on the surface of the multi-doped lithium manganese oxide particles, and 0.47nm is the lattice width corresponding to the (111) crystal plane of lithium manganese oxide; Figure 5(d) is a TEM image corresponding to the lithium manganese oxide material containing a coating layer of Figure 5(b), which shows that there is a LaAlO3 coating layer of relatively uniform thickness on the outer surface of the multi-doped lithium manganese oxide particles, which proves the existence of the coating layer and the thickness of the coating layer can be measured.

[0107] (3) EPMA test was carried out using JEOL / JXA-iHP200F of Japan Electronics. The powder and epoxy resin were evenly mixed, mounted, metallographically polished, and then placed under an electron microscope for observation. The distribution of the coating layer and the type and content of the elements in the bulk and coating layer could be obtained.

[0108] FIG6(a) is a cross-sectional EPMA test diagram of the lithium manganese oxide material containing a coating layer obtained in Example 1, and FIG6(b) is a distribution diagram of the manganese element obtained after a scanning test corresponding to FIG6(a). The manganese element is marked in cyan, showing that the manganese element is uniformly distributed as a whole; FIG6(c) is a distribution diagram of the aluminum element obtained by scanning the test, and the aluminum element is marked in blue, showing that the distribution of the aluminum element is mainly concentrated at the edge of the lithium manganese oxide particles, that is, the aluminum element is mainly distributed on the outer surface of the lithium manganese oxide particles, proving that the aluminum exists in the form of a coating layer rather than uniform bulk doping. The EPMA test can automatically detect and identify the element and confirm that the surface coating element is aluminum; similarly, FIG6(d) is a distribution diagram of the lanthanum element obtained by scanning. The distribution of lanthanum is similar to that of aluminum, and is concentrated at the edge of the cross-sectional lithium manganese oxide particles, that is, the outer surface, proving that lanthanum exists in the form of a coating layer.

[0109] (4) ICP (inductively coupled plasma) test is performed to detect the chemical composition of the substance, and the percentage of each component can be determined. The lithium manganese oxide material containing the coating layer obtained in Example 1 is tested, and the test result is the result of the sum of the element contents of the multi-doped lithium manganese oxide and the coating layer material. Then, according to the difference in the elements contained in the multi-doped lithium manganese oxide and the coating layer material, the specific composition of the multi-doped lithium manganese oxide can be determined. By combining the above characterizations (1), (2) and (3), the percentage, element content and thickness of the coating layer can be further determined.

[0110] II. Characterization of Mn with different valence states:

[0111] Using XPS characterization technology, before the formal test, the powder is first etched to a depth of 5nm by argon ions to remove the surface coating layer, reducing the influence of low-valent elements in the surface coating layer on the average valence state of Mn. After testing, a relatively accurate signal peak of the Mn element is obtained. According to the test results, a quantitative analysis of the Mn content in different valence states is performed to determine the average valence state of Mn in the material.

[0112] Figure 4 This is the XPS test chart of the manganese element of the lithium manganate material obtained in Example 1. After peak fitting processing, the Mn content in different valence states is obtained, and the average valence state of Mn is further calculated. The results of other embodiments and comparative examples are recorded in Table 1.

[0113] III. Mn dissolution test:

[0114] The powder was weighed in a certain proportion and added to the electrolyte, and then allowed to stand at 45°C for 7 days. After filtering, the electrolyte was taken for ICP testing to determine the content of Mn ions dissolved in the electrolyte. The results are recorded in Table 1.

[0115] Ⅵ. Electrode preparation and electrical performance testing:

[0116] The lithium manganese oxide material, the combined conductive agent, and PVDF of Example 1 were mixed in a mass ratio of 93:4:3 to prepare a positive electrode slurry, which was coated on an Al foil and vacuum dried at 120°C, cold pressed, and cut into pieces to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet was 15 mg / cm 2 The electrolyte used is conventional lithium manganese oxide electrolyte. Metal Li negative electrode is used, assembled into button cell, the voltage range of the test is 3.0~4.35V, constant current constant voltage charging is adopted, first 2 cycles of charge and discharge test are carried out at 0.1C rate, and then 60 cycles of charge and discharge cycle test are carried out at 1C rate; the results are as follows Figure 1 and Figure 2 As shown, other results are recorded in Table 1;

[0117] In the full-electric test, the negative electrode uses a fast-charging graphite negative electrode. The positive electrode sheet containing 1% manganese oxide material of No. 14 is obtained as described above and assembled into a soft-pack battery with a battery capacity of 0.8Ah. After the formation process, the battery is cycled at room temperature (25°C) and high temperature (45°C) at a rate of 1C, and the number of charge and discharge test cycles when the capacity reaches 80% of the first charge capacity is recorded. The results are as follows Figure 3 As shown, the results of other embodiments and comparative examples are recorded in Table 1.

[0118] Table 1

[0119]

[0120] It can be seen from Table 1 that:

[0121] Examples 1-5 are some classic examples of lithium manganese oxide materials that meet the requirements of the present invention; Comparative Example 1 is a basic sample that is not doped or modified but only coated. Compared with the samples in each embodiment, the structural stability of the material is slightly poor, so the full-electric room temperature and high temperature cycle performance is poor, and the capacity decays to 80% of the initial capacity within a relatively small number of charge and discharge cycles.

[0122] Compared with the basic sample of comparative example 1, Example 1 co-doped high-valent element Nb with low-valent Cr and Sr. Due to the control of the doping amount and the average valence state of the doped elements, the battery capacity was almost not affected and the capacity was not reduced. However, the performance was greatly improved and enhanced in terms of full-electric room temperature and high-temperature cycles, which fully demonstrated that the synergistic effect of high-valent elements in increasing capacity and low-valent elements in improving structural stability was fully realized. In addition, compared with comparative example 4, the outer layer of the coating of low-valent transition metal composite oxide LaAlO3 with a perovskite structure has a more prominent effect on improving cycle performance. The material has a stronger structural stability and can better resist the corrosion of HF in the electrolyte.

[0123] In Examples 2 to 5, after partially replacing pentavalent Nb with higher-valent W (hexavalent), a larger amount of low-valent elements can be introduced according to the strategy of an average valence state of the doping element of 3.5, thereby further improving the structural stability of the material. Therefore, there are different degrees of improvement in all-electric room temperature and high-temperature cycles.

[0124] The lithium manganate material obtained in Comparative Example 2 is a conventional low-valent cation Mg single-doped sample. Compared with Example 1, the charge and discharge capacity is significantly reduced, but the cycle performance of the charge and discharge is slightly better. This is because the doping of low-valent Mg ions increases the average valence of Mn, and Mn 3+ The content of Mn decreases, resulting in a decrease in capacity, but the increase in the average valence of Mn reduces the occurrence of the Jan-Taylor effect and reduces the Mn 2+The dissolution of the material enhances the structural stability and thus the cycle performance is significantly improved.

[0125] Comparative Example 3 shows that the lithium manganate material obtained is a single doping verification of high-valent cations, Nb 5+ The doping of Mn reduces the average valence of Mn. 3+ The content of Mn increases 4+ The content of Mn is reduced, so the first cycle charging capacity of the battery is increased, but 4+ The reduction of Mn content makes the structural stability of the material worse. 3+ The disproportionation reaction of Mn 2+ The dissolution of the electrode increases and the Jiang-Taylor effect intensifies, resulting in a significant deterioration in the power-off and full-electric cycle performance.

[0126] Comparative Example 4 adopts a conventional Al2O3 coating process. Compared with LaAlO3, ZnAl2O4, etc. with perovskite or spinel structures having stronger structural stability and acid and alkali resistance in Examples 1 to 5, it has slightly poorer corrosion resistance to HF generated by trace water in the electrolyte, and is more prone to surface corrosion of the material and Mn dissolution, so the full electric cycle performance is slightly reduced.

[0127] Examples 1, 6, 7 and comparative examples 5 and 6 are respectively the average valence state of the doping element E = 3.5, 3.4, 3.6, 3.3, 3.7. By comparison, it can be seen that when E is 3.3 and 3.7, it will cause obvious capacity reduction or cycle deterioration; Examples 1, 8, 9, 10 and 11 are respectively the comparison of different coating agent contents of 1.5wt%, 1.0wt%, 2.0wt%, 0.3wt%, 2.5wt% under the same coating agent material. When the coating amount is 0.3wt% too low, the LMO surface cannot be well coated, and it suffers from electrolyte corrosion and Mn dissolution, resulting in deterioration of the cycle. When the coating amount is too high, the transmission of ions and electrons is hindered, resulting in a decrease in capacity.

[0128] The second sintering temperature in Example 13 is similar to that in Example 1, and the product performance is similar; the temperature of the second sintering of the coating in Example 12 is relatively low, the bonding force between the coating agent and the multi-doped lithium manganese oxide body is insufficient, the interaction force between the materials is weak, and it cannot well resist the corrosion of the electrolyte solvent and acidic HF to the lithium manganese oxide, and the cycle is slightly deteriorated; in Examples 14 and 15, the temperature of the second sintering of the coating gradually increases, and excessively high temperature will cause the low-valent elements in the coating agent to diffuse into the main body of the multi-doped lithium manganese oxide, the average valence state of manganese will increase, the material capacity will decrease, and the excessively high sintering temperature will cause the lithium manganese oxide to be deoxidized, the oxygen defects in the bulk structure will increase, and the cycle performance will deteriorate to a large extent.

[0129] From the above, it can be seen that the present invention makes full use of the synergistic effect of mixed doping of multiple transition metal cations through the solution of multi-valent mixed doping of high-valent transition metal cations (V, VI) and low-valent transition metal cations (II, III). Low-valent cations improve the structural stability of lithium manganese oxide, and high-valent cations improve the average content of trivalent manganese ions to neutralize the capacity reduction problem caused by the increase in the average valence state of manganese caused by low-valent cation doping. This innovative doping method can not only improve the structural stability of lithium manganese oxide, but also maintain its high capacity, effectively solving the problem of reduced material capacity caused by the doping process in the prior art.

[0130] At the same time, the present invention effectively solves the problem of near-surface Mn after doping with high-valent metal elements through epitaxial coating of low-valent transition metal composite oxides. 3+ The problem of increased Mn dissolution and cycle deterioration caused by increased concentration. Through epitaxial coating of low-valent metal element composite oxides, a small amount of surface doping is achieved to balance the reduction of Mn valence caused by high-valent element doping, reduce Mn dissolution, and at the same time isolate LMO from direct contact with the electrolyte through coating, reduce HF and other corrosion of LMO, and further improve the cycle. The metal elements in the coating material are limited to elements with conventional oxidation valence states of +2 and +3, and low-valent transition metal composite oxide materials with higher structural stability and acid and alkali resistance, and perovskite structure or spinel structure are selected, and conventional transition metal oxide materials such as Al2O3 and MgO can be discarded.

[0131] The Mn dissolution amount of the lithium manganate material obtained by the present invention can reach 800-1400ppm, further controllable to 800-1200ppm, and further controllable to 800-1100ppm; the 0.1C charging capacity assembled using the lithium manganate material is ≥130mAh / g, the first cycle coulomb efficiency is ≥95%, and the capacity retention rate of 60 cycles at 1C rate is ≥97%; the assembled full battery has a room temperature cycle of ≥1500 cycles and a high temperature cycle of ≥600 cycles. These performance indicators are significantly better than the prior art, indicating that the lithium manganate of the present invention has significantly improved high temperature performance and cycle stability.

[0132] The technical solution of the present invention mainly involves the fields of "material science", "electrochemistry" and "energy storage", and has broad application prospects. It can be applied not only to power lithium-ion batteries for electric vehicles, but also to other electronic devices that require high energy density, long life and good charging performance. The promotion and application of this technology is expected to promote technological progress in the fields of electric vehicles and energy storage.

[0133] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0134] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0135] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A lithium manganate material, characterized in that: A multi-doped lithium manganate having a spinel structure, wherein the chemical formula of the multi-doped lithium manganate is Li 1+x Mn 2-y-z A y B z O4, 0.04≤x≤0.15, y≤0.02, y+z≤0.10; A and B are doping elements, and A is a high-valent transition metal, and B is a low-valent transition metal; E A is the oxidation state of A, E B is the oxidation state of B, E is the average valence state of the doping element, and E=(E A *y+E B *z) / (y+z), 3.4≤E≤3.6; the outer surface of the multi-doped lithium manganate also has a coating layer, the coating layer includes divalent and / or trivalent transition metal elements, and the coating layer is a perovskite structure and / or a spinel structure.

2. The lithium manganate material according to claim 1, characterized in that: 3.48≤E≤3.52。 3. The lithium manganate material according to claim 1 or 2, characterized in that: A comprises a transition metal element having a pentavalent or hexavalent oxidation state, and A comprises at least one of Nb, Mo or W; Preferably, the B includes a transition metal element having a divalent or trivalent oxidation state, and B includes at least one of Mg, Zn, Sr, Al, Cr, Co or Ni.

4. The lithium manganate material according to any one of claims 1 to 3, characterized in that: The coating layer comprises a composite oxide of a divalent and / or trivalent transition metal element; the composite oxide comprises at least one of LaAlO3, LaNiO3, SrAl2O4 or ZnAl2O4; Preferably, based on the mass of the multi-doped lithium manganate being 100%, the mass of the coating layer accounts for 0.5% to 2%, preferably 1.0% to 1.5%.

5. A method for preparing the lithium manganate material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Mixing a lithium source, a manganese source, and additives containing A and B separately or simultaneously, and performing a first sintering to obtain multi-element doped lithium manganate; The obtained multinary doped lithium manganate is mixed with a coating agent, and a second sintering is performed to form a coating layer to obtain a multinary doped lithium manganate material.

6. The method for preparing the lithium manganate material according to claim 5, characterized in that: The lithium source includes at least one of Li2CO3, LiOH·H2O or LiNO3; Preferably, the manganese source comprises at least one of Mn3O4, MnO2, Mn2O3 or MnCO3; Preferably, the additives containing A and B separately or simultaneously include at least one of oxides, hydroxides, carbonates, oxalates or nitrates, preferably oxides and / or hydroxides; Preferably, the particle size of the additives containing A and B separately or simultaneously is ≤1 μm; Preferably, the amounts of the lithium source, the manganese source, and the additives containing A and B separately or simultaneously are controlled according to the stoichiometric ratio in the chemical formula of the multi-doped lithium manganate; Preferably, the coating agent comprises a composite oxide of a divalent and / or trivalent transition metal element; the composite oxide comprises at least one of LaAlO3, LaNiO3, SrAl2O4 or ZnAl2O4; Preferably, the particle size D of the coating agent is 50 It is 100nm~5μm.

7. The method for preparing the lithium manganate material according to claim 5 or 6, characterized in that: The first sintering process includes firstly heating the temperature to 450-650°C at a heating rate of 2-5°C / min and keeping the temperature for 4-8 hours for a first stage of pre-sintering, and then continuing to heat the temperature to 700-850°C and keeping the temperature for 9-11 hours for a second stage of sintering; Preferably, the first sintering is performed in an oxidizing atmosphere, and the oxidizing atmosphere includes air or oxygen-enriched air; Preferably, after the first sintering, the sintered sample is sequentially crushed, sieved and iron-removed.

8. The method for preparing the lithium manganate material according to any one of claims 5 to 7, characterized in that: The second sintering process includes first heating the temperature to 700-800°C at a heating rate of 2-5°C / min and keeping the temperature for 1-3 hours for primary sintering, and then cooling the temperature to 500-650°C and keeping the temperature for 7-9 hours for secondary sintering; Preferably, after the second sintering, the sintered sample is sequentially crushed, sieved and iron-removed.

9. A positive electrode sheet, characterized in that: The positive electrode plate contains the lithium manganese oxide material according to any one of claims 1 to 4.

10. A battery, characterized in that: The battery contains the positive electrode sheet according to claim 9 or the lithium manganese oxide material according to any one of claims 1-4.